Forest preservation and forest law - Johnston, E. M. (My University, 1908)
Introduction: In this short treatise of an almost inexpansible subject it will be our aim to treat only in general of the two topics chosen above, and give in brief their influence in general upon practical forestry as practiced today. Of all of our natural resources there is none of more importance to the general welfare of mankind than the forests.
Citation: Johnston, E. M. Forest preservation and forest law. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Forests; Legislation; Trees; Forestry; Graduating theses; Senior theses; Theses